Implementasi Sistem Lampu Otomatis Berbasis Internet of Things (IOT): Penelitian - Weny Nur Afdilla Simangunsong; Dicky Apdillah; Dini Farhatun; Zulfa Ar Rahman (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
The use of lighting systems is still commonly controlled manually, which often leads to inefficient electricity consumption, especially when lights remain on while not in use. This study aims to design and implement an automatic lighting control and monitoring system based on the Internet of Things (IoT). The research method applied is an experimental method consisting of system design, implementation, and testing stages. The system is developed using NodeMCU ESP8266 as the main controller, a relay as the actuator, and an LDR sensor to detect ambient light intensity. The test results indicate that the system is capable of controlling lights automatically and manually through a web-based monitoring interface with reliable performance. The implementation of this system reduces dependence on manual operation and improves electrical energy efficiency. Therefore, the proposed IoT-based lighting control and monitoring system can serve as an alternative solution to optimize energy usage in residential and public facilities.